LOCAL WISDOM IN THE SOUTH SULAWESI FOLKTALE PUTRI TANDAMPALIK - Afriani Ulya (Seshiski: Southeast Journal of Language and Literary Studies, 2025)
This research aims to analyze the local wisdom in the folktale of South Sulawesi, Putri Tandampalik. The research method used is the qualitative descriptive method. The research data consists of events depicted in the folktale of Putri Tandampalik, which is also used as the data source. The folktale that serves as the data source for this research is published by the Malay Cultural Research and Development Center under the title 366 Cerita Rakyat Nusantara. The data collection technique was carried out using careful reading and note-taking methods. Data analysis and interpretation were conducted lexically and contextually, primarily concerning local wisdom formulated verbally and nonverbally. The research results show that the folktale of Putri Tandampalik reflects the social interaction habits of the people of South Sulawesi and the values contained in the folktale, which include moral and educational values, especially the cultural values of South Sulawesi known as Siri na Pacce culture. The Siri na Pacce culture is one of the cultural values that calls for mutual respect among fellow humans and Siri na Pacce is an attitude and determination that arises within a person to achieve a life goal.